Plataformas Zoom y Microsoft Teams como una aplicación para la comunicación en la Unidad Educativa La Maná, durante la pandemia 2020 - Oña Toapanta, Evelyn Selene (2021)
At the beginning of 2020, a pandemic called “COVID-19” originated, without imagining that this would generate great changes worldwide; having to adapt from one moment to another to a new way of life, being affected several situations, especially the educational system. At the global level, confinement was taken as a measure so as not to risk everyone's health, so several institutions closed their facilities proceeding to a new mode of communication between teacher-student, making use of new techniques and technological tools. Zoom and Microsoft Teams, virtual platforms used for video calls; in which all the students are seeing and listening to what the teacher is teaching in his class, which comes to do almost the same as what he previously did in the face-to-face mode, the information transmitted is understandable with the help of the tools that these applications offers, although there are few cases in which communication fails; either due to problems or lack of technological resources. In the present investigation, it was analyzed and determined how Zoom and Microsoft Teams is an application in terms of teacher-student communication at La Maná Educational Unit. Using descriptive research as a method; either the interviews and surveys that allowed us to collect and obtain data.